High dietary fat intake increases fat oxidation and reduces skeletal muscle mitochondrial respiration in trained humans - Leckey, J. J.; Hoffman, N. J.; Parr, E. B.; Devlin, B. L.; Trewin, A. J.; Stepto, N. K.; Morton, J. P.; Burke, L. M.; Hawley, J. A (The FASEB Journal, 2018)
High-fat, low-carbohydrate (CHO) diets increase whole-body rates of fat oxidation and down-regulate CHO metabolism. We measured substrate utilization and skeletal muscle mitochondrial respiration to determine whether these adaptations are driven by high fat or low CHO availability. In a randomized crossover design, 8 male cyclists consumed 5 d of a high-CHO diet [>70% energy intake (EI)], followed by 5 d of either an isoenergetic high-fat (HFAT; >65% EI) or high-protein diet (HPRO; >65% EI) with CHO intake clamped at <20% EI. During the intervention, participants undertook daily exercise training. On d 6, participants consumed a high-CHO diet before performing 100 min of submaximal steady-state cycling plus an ~30-min time trial. After 5 d of HFAT, skeletal muscle mitochondrial respiration supported by octanoylcarnitine and pyruvate, as well as uncoupled respiration, was decreased at rest, and rates of whole-body fat oxidation were higher during exercise compared with HPRO. After 1 d of high-CHO diet intake, mitochondrial respiration returned to baseline values in HFAT, whereas rates of substrate oxidation returned toward baseline in both conditions. These findings demonstrate that high dietary fat intake, rather than low-CHO intake, contributes to reductions in mitochondrial respiration and increases in whole-body rates of fat oxidation after a consuming a high-fat, low-CHO diet.